2010
DOI: 10.1007/s10265-009-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

Unique cellular effect of the herbicide bromoxynil revealed by electrophysiological studies using characean cells

Abstract: In a previous paper, we proposed that the primary action of the herbicide bromoxynil (BX; 3,5-dibromo-4-hydroxybenzonitrile) is cytosol acidification, based on the fact that bromoxynil induced the inhibition of cytoplasmic streaming and cell death of Chara corallina in acidic external medium (Morimoto and Shimmen in J Plant Res 121:227-233, 2008). In the present study, electrophysiological analysis of the BX effect was carried out in internodal cells of C. corallina. Upon addition of BX, a large and rapid pH-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This may cause transient increases in herbicide concentrations in adjacent freshwater ditches and subsequently in watercourses into which these drain. Although the effects of raised herbicide concentrations on angiosperms2, 3 and animals4, 5 have been investigated, far‐reaching potential effects may also occur in relation to primary producers which in freshwater aquatic environments include various algal species 6, 7. These organisms are very sensitive to perturbations in the chemical environment, and changes in the abundance or pattern of algae in a freshwater course may affect organisms higher up the food chain that feed on them.…”
Section: Introductionmentioning
confidence: 99%
“…This may cause transient increases in herbicide concentrations in adjacent freshwater ditches and subsequently in watercourses into which these drain. Although the effects of raised herbicide concentrations on angiosperms2, 3 and animals4, 5 have been investigated, far‐reaching potential effects may also occur in relation to primary producers which in freshwater aquatic environments include various algal species 6, 7. These organisms are very sensitive to perturbations in the chemical environment, and changes in the abundance or pattern of algae in a freshwater course may affect organisms higher up the food chain that feed on them.…”
Section: Introductionmentioning
confidence: 99%
“…CX is a benzonitrile herbicide and its analogues, BX and IX, bind the D1 protein in photosystem II and inhibit electron transport, which induces degradation of the D1 protein [ 46 ]. Moreover, previous studies reported that BX treatment inhibits the electrogenic proton pump by cytosol acidification [ 47 , 48 ]. Therefore, it is likely that that CX acts in a similar herbicidal mechanism to BX and IX.…”
Section: Discussionmentioning
confidence: 99%
“…Characeae is also useful in studying the electrical response to various stresses; mechanical stimulation (Kishimoto 1968;Shimmen 1996Shimmen , 1997aShimmen , b, c, 2001bShepherd et al 2001;Iwabuchi et al 2005Iwabuchi et al , 2008Kaneko et al 2005), aluminum (Takabatake and Shimmen 1997) and herbicide (Shimmen 2010).…”
Section: Introductionmentioning
confidence: 99%